Development of Google Sites–Based Multimedia for Social Science Learning to Improve Fifth-Grade Computational Thinking Skills - Usmaulidar; Yeni Erita; Leni Zahara; Muhammadi (Jurnal Penelitian Pendidikan IPA, 2026)
This research is motivated by the limited use of interactive multimedia in science learning in elementary schools, resulting in suboptimal student engagement and the development of computational thinking skills. The textbook-dominated learning process results in students being less active and having difficulty understanding concepts in depth. Therefore, the use of interactive multimedia based on Google Sites is expected to increase student motivation, understanding, and active participation. The purpose of this research is to develop interactive multimedia based on Google Sites in fifth-grade science learning in elementary schools that is highly valid, practical, and effective in improving students' computational thinking skills. The method used was Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of fifth-grade teachers and students at SDN 11 Lubuk Buaya and SDN Percobaan in Padang City, West Sumatra. Data were collected through observation, interviews, questionnaires, and computational thinking tests. Data analysis techniques included validity, practicality, and effectiveness tests. The practicality test was conducted in class VB at SDN 11 Lubuk Buaya with 17 students and class VB at SDN Percobaan with 24 students, and 2 class teachers in each class. The effectiveness test was conducted in class VA at SDN Percobaan with 23 students as the control class and class VB as the experimental class. The validation results showed a score of 90% from the material experts, 93% from the language experts, and 81% from the design experts, categorizing it as very valid. The practicality test obtained a score of 95% from the teachers and 92% from the students, categorizing it as very practical. The effectiveness test showed that the experimental class achieved an average score of 87.44 (effective), while the control class achieved 58.88 (moderately effective). Thus, the Google Site-based interactive multimedia was declared very valid, very practical, and effective as an alternative learning medium for science studies in elementary schools.